2009
DOI: 10.1039/b902787d
|View full text |Cite
|
Sign up to set email alerts
|

Autoionizing resonances in time-dependent density functional theory

Abstract: Autoionizing resonances that arise from the interaction of a bound single-excitation with the continuum can be accurately captured with the presently used approximations in time-dependent density functional theory (TDDFT), but those arising from a bound double excitation cannot. In the former case, we explain how an adiabatic kernel, which has no frequency-dependence, can yet generate the strongly frequency-dependent resonant structures in the interacting response function, not present in the Kohn-Sham respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The current XC functionals for TDDFT are known not to perform well in all cases, but they perform adequately in many cases and are under active development. 7,8 The time-propagation approach has also advantages from the numerical point of view, which makes it suitable for large systems. The computational cost scales well with respect to increasing system size, 9 and it allows efficient parallelization over TDKS states.…”
Section: Introductionmentioning
confidence: 99%
“…The current XC functionals for TDDFT are known not to perform well in all cases, but they perform adequately in many cases and are under active development. 7,8 The time-propagation approach has also advantages from the numerical point of view, which makes it suitable for large systems. The computational cost scales well with respect to increasing system size, 9 and it allows efficient parallelization over TDKS states.…”
Section: Introductionmentioning
confidence: 99%
“…The description of autoionizing resonances arising from double excitations is problematic in TDDFT. However, in the present work resonance phenomena primarily arise from single excitations which are described well using TDDFT [49]. In particular, previous TDDFT studies of photoionization of acetylene have shown a good level of accuracy [15].…”
Section: A Tddft Description Of the Electronic Dynamicsmentioning
confidence: 91%
“…Due to the electron-electron interaction these discrete states couple to the continuum leading to emission of an electron. Previous studies of this process within TDDFT have been concentrated on the linear response regime [12]. It is well known that doubly excited states can only be described in a TDDFT treatment if the exchange-correlation kernel is frequency dependent [3].…”
Section: Introductionmentioning
confidence: 99%